Differences in the Course of Rehabilitation and Outcomes for Publicly Insured Pediatric Patients After Anterior Cruciate Ligament Reconstruction. Issue 5 (31st May 2022) - Greenberg, Elliot; Butler, Lauren; Giampetruzzi, Nicholas; Link, Meredith; Prati, Victor; Weaver, Adam; Saper, Michael
Background: Previous research has demonstrated individuals with public insurance may encounter delays accessing care and experience different orthopedic management for musculoskeletal injuries. Rehabilitation after anterior cruciate ligament reconstruction (ACLR) is critical to optimize outcomes. The effect of insurance status on rehabilitation practice and patient outcomes among youth athletes has not been explored. Purpose: To examine the effect of insurance type (public vs private) on physical therapy (PT) visit utilization and outcomes within pediatric and adolescent patients after ACLR. Methods: This was a sub-analysis of a larger retrospective dataset of patients who underwent primary ACLR between 2013 and 2019 at 5 institutions. All patients followed a structured rehabilitation protocol as directed by the treating institution and completed a battery of return to sport (RTS) tests which included single-legged hop testing. PT visit frequency was assessed both overall and by time period (first 6 weeks, week 7-month 3, 3-6 months, and 6+ months). PT visits were recorded up until the time of last recorded hop test within 12 months post-surgery. The average number of visits attended per week during the observed time was calculated for each patient. The effect of insurance status on PT management was analyzed using T-tests. The effect of insurance status on the odds of passing hop tests was assessed using multivariable logistic regression with a random effect of site. Adjusted models controlled for time to test in months. An alpha level of p<0.05 was used to determine significance. Results: 281 (15.7 ± 1.9 years, 58% male) patients were included in this analysis. The groups were demographically similar, with 45.5% classified as having public insurance. (Table 2) Patients with public insurance experienced a longer delay from surgery to the time of hop test (8.3±2.2 vs 7.7±1.5 months, p=0.009) and had a lower number of PT visits per week (0.92±0.37 vs 1.04±0.38, p=0.005). Publicly insured subjects attended fewer PT visits from week 7-3 months (1.06±0.50 vs 1.26±0.52, p=0.001) and 3-6 months (0.88±0.45 vs 0.99±0.45, p=0.04). Insurance status had a statistically significant effect (p=0.01) on the odds of passing the single leg hop test (OR, 2.72; 95% CI, 1.27-5.81) and was nearly significant (p=0.06) for all hop tests (OR, 1.74; 95% CI, 0.98-3.07). Conclusion: Publicly insured youth athletes average a lower number of weekly PT visits, experienced a longer delay from surgery to hop test and were 2.7 times less likely to pass the single leg hop test. Table 1. Table 2. Demographics